Organizational climate and satisfaction of the external user in the hospitalization services of the Instituto Nacional de Salud del Niño, 2017 - Fernández-Oliva, Danitza (2019)
Introduction. The organizational climate within health institutions and patient satisfaction are used to evaluate and improve the quality of health services. Objective. Determine the organizational climate and the satisfaction of the external user regarding the medical care received in the hospitalization services of the Instituto Nacional Salud del Niño (INSN). Methods. In the year 2017 a survey was applied to qualify the organizational climate to the workers of the hospitalization services of the Department of Medicine of the INSN. The satisfaction of the external user was measured through the SERVQUAL survey applied to external users. Results. The qualification of the organizational climate was 76,3%, considered as improvable; and the overall satisfaction of the external user was 64,4%. The organizational climate in the dimensions of identity, organizational communication and structure achieved the qualification of healthy and the remuneration dimension obtained the qualification of unhealthy. The dimension best valued by external users was: during your hospitalization did you receive a medical visit every day? and the least valued: were the procedures for discharge high?. Conclusion. The overall rating of the organizational climate was 76,3% and the overall satisfaction of the external user was 64,4% in the INSN.